The Effect of Interpersonal Relationships on the Employment of People with Developmental Disabilities: The Mediating Effect of Self-esteem - Ok Kim, Mi; in Kang, Hye; won Song, eong (International Journal of Psychosocial Rehabilitation, 2019)
The purpose of this study was to examine the effect of interpersonal relationships on the employment of people with developmental disabilities by focusing on the mediating effect of self-esteem and to provide support for those with developmental disabilities in poor employment conditions. The subjects for analysis were 402 people with developmental disabilities (371 individuals with intellectual disabilities and 31 individuals with autism) aged 18 or older who responded to the third survey of the second wave of the Employment Panel for the Disabled at the Korea Employment Agency for Persons with Disabilities in 2018. For analysis, SPSS 22.0 and AMOS 22.0 were utilized according to the purpose of the study. A technical analysis of the major variables was conducted, and structural equations and bootstrap analysis were performed to examine whether self-esteem mediates the effects of interpersonal relationships on the employment of people with developmental disabilities. The main results of this study are as follows. First, the interpersonal relationships among people with developmental disabilities were found to have a positive (+) effect on employment. Second, such relationships were found to have a positive (+) effect on self-esteem. Third, self-esteem was found to have a partial mediating effect on the relationship between the interpersonal relationships among people with developmental disabilities and employment. The research findings suggested the necessity of establishing networks within local communities for people with developmental disabilities, the need to revitalize self-esteem improvement programs, and the implications for employing said people. This study is meaningful in that it identified the employment-related factors of people with developmental disabilities through psychosocial variables and provided the necessary data.